Synthesis and evaluation of undoped and silver and copper doped lithium tetraborate nanoparticles as thermoluminescence dosimeter - Khalilzadeh, Nasrin (2014)
Tissue equivalent thermoluminescence dosimeters (TLDs) are commonly used for monitoring dose of ionizing radiation as personal or medical radiation dosimeters. The commercially available macro-scale lithium tetra borates (LTB) have several drawbacks such as poor Thermoluminescent (TL) intensity, limited dose linearity, losses information with time (fading) and energy dependence,which might be improved by using nano-scale activated LTB, the main goal of this study. LTB is the most popular material for radiation dosimetry because of its effective atomic number (Zeff = 7.4) that close with the Zeff of human tissue (7.42). Furthermore, LTB is almost stable chemical compound and can be easily doped with TL sensitizers. In line with this development the objectives of this work were to synthesize and to investigate the structural characteristics and TL properties of undoped LTB and silver and copper doped LTB (LTB-Ag and LTB-Cu) nanoparticles for dosimetric applications. The LTB nanoparticles were synthesized by using innovative single step thermal treatment method. Subsequently, the samples were investigated for thermal stability and phase transition using thermal gravimetric analysis (TGA), derivative thermogravimetry analysis (DTG), and differential scanning calorimetry (DSC). The TGA, DTG, and DSC results showed the triple phases of mass loss were observed. Fourier transform infrared spectroscopy (FT-IR) was used to monitor the formation nanoparticles in the range of 200-4000 cm-1. The samples were subjected to different calcination temperatures and found 650, 700, and 750 oC were the principal calcination temperatures based on the X-ray diffraction (XRD) patterns and transmission electron microscopy (TEM) images. To study the effect of PVP capping agent for regulating nanoparticles’ agglomeration,0.009, 0.018, and 0.027 mol of PVP concentrations were used. The narrowest particle size and size distributions were reached at 0.027 mol of PVP for LTB and LTB-Cu nanoparticles and at 0.018 mol of PVP for LTB-Ag nanoparticles. The average particle sizes determined from TEM size distributions were 3.34,4.61, and 4.56 nm for LTB, LTB-Cu and LTB-Ag nanoparticles, respectively at calcination temperature of 750 oC. The UV-visible spectroscopy (UV-Vis) was used to determine the optical bandgap of the synthesized nanoparticles. To investigate the TL property of the synthesized nanoparticles, dose response,energy storage ability, and energy dependence of nanophosphors were studied from glow curve of dose response at a variety of dose ranges of 0.005, 0.01, 0.1,0.5, 1, 10, 100, and 150 Gy. The current nano-scale doped and undoped LTB dosimeters have good physical properties and TL response that they can be produced easily by single step thermal treatment method at effective cost and without by-product effluents.